Multimeter dengan Sistem Penayangan Data Berbasis Web dan Kacamata Data - Tommy Alexy; Rian Ferdian (Universitas Andalas, 2023)
This study aims to create a multimeter system that is able to use with database system and see with data glasess . Multimeter is a measuring instrument used for measurements on electronic compositions. Electricity is indispensable today but if not careful electricity will be very dangerous. One of the dangers of electricity is the occurrence of electric arcs, electric arcs occur due to the presence of dielectric materials that result in electrode charge transfer. Practical learning of electronics is directly related to electricity so careful observation is needed, especially when measuring the three main quantities in the flow of electricity. This system is expected to help users in observing electrical components such as electrical voltage (Voltage / V) and electrical resistance (Ohm / Î©). The system uses a zmpt101b sensor used for voltage readings using a mean system that is taking some electric current data in a certain period of time and taking an average reading of the current read by the sensor, the voltage sensor is used for voltage readings using a mean system that is taking some voltage data in a certain period of time and taking an average voltage read by the sensor, in reading resistance researchers use the voltage divider formula to find out how much is in a resistor that is not known how much resistance. The information obtained will be displayed on the website so that users can more easily sort the readings on the amount of electricity read by the multimeter.